Evaluation of the Compliance with Health Protocols among the Production Section Workers at a Manufacturing Industry in Surabaya - Rendhar Putri Hilintang; Meirina Ernawati (Universitas Airlangga, 2022)
Introduction: The growth of COVID-19 cases in Indonesia has continued to increase which might have the effect of reducing the productivity levels in the industrial sector. The Ministry of Manpower has called on every company to establish health protocols related to preventing the transmission of COVID-19 in the workplace. The purpose of this study was to describe the compliance with the existing health protocols at PT Albea Rigid Packaging Surabaya. Methods: The population in this study was the workers in the production section and the sample was selected using the simple random sampling technique. The variables in this study were physical distancing, hand-washing-with-soap behavior, temperature checking, sunbathing, and the usage of surgical masks, hand sanitizer, gloves, and face shields. The data collection was carried out using an observation form checklist. Result: PT Albea Rigid Packaging Surabaya has referenced the letter circulated by the Office of Manpower and Transmigration of East Java Province and Regulation of the Mayor of Surabaya No. 28 of 2020 concerning the Guidelines for the New Normal Order of COVID-19. The health protocols implemented at PT Albea Rigid Packaging Surabaya included the implementation of physical distancing, hand-washing-with-soap behavior, temperature checking, sunbathing, and the usage of surgical masks, hand sanitizer, gloves, and face shields. Health protocol temperature checking already has a 100% compliance rate in all departments but for the sunbathing protocol, the compliance is still at 0% in all departments. Conclusion: The compliance of workers in the production section of PT Albea Rigid Packaging Surabaya with the health protocol is still not running optimally.